Green Innovation, Renewable Energy, and Institutional Quality in Driving CO₂ Emission Decoupling: Evidence from Developing Countries - Deni Kusumawardani; Lilik Sugiharti; Ryan Anward (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This study examines CO₂ emission decoupling in developing countries as a broader indicator of sustainable economic performance, not merely as emission reduction. Specifically, it analyzes the roles of green innovation, renewable energy consumption, and institutional quality in explaining whether economic growth can be increasingly separated from CO₂ emissions through technological capability, energy-system transition, and governance capacity. Using panel data from 34 developing countries over the period 2002–2021, the study applies the Tapio decoupling index to measure CO₂ emission decoupling status and transforms the resulting classification into an ordinal variable with three categories: negative decoupling, coupling, and decoupling. The determinants of decoupling status are analyzed using a panel generalized ordered logit model with average marginal effects estimation. The results show that green innovation significantly increases the probability of being in the decoupling category and emerges as the strongest positive determinant of decoupling performance. Renewable energy consumption also has a positive but marginally significant effect, indicating that renewable energy has begun to contribute to decoupling in developing countries, although its effect remains relatively modest. Institutional quality is negatively associated with decoupling, while its interaction with renewable energy is not statistically significant. Population also has a significant negative effect on the probability of decoupling. Overall, the findings suggest that decoupling in developing countries is driven more strongly by green innovation than by renewable energy or institutional quality, while governance improvements have not yet been fully translated into effective low-carbon transition outcomes.